POLYMORPHIC VARIANTS OF SUNFLOWER RFL-PPR GENES AS MOLECULAR GENETIC MARKERS - I. N. Anisimova; Yu. I. Karabitsina; N. V. Alpatieva; E. B. Kuznetsova; V. A. Gavrilova; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
A sample of 131 sunflower lines from VIR genetic collection which differed for the ability to suppression of the CMS phenotype was studied using molecular markers specific for the CMS PET1 associated mitochondrial locus orfH522 and Rf1 nuclear gene, and also for CAPS-markers developed on the bases of single nucleotide polymorphism of RFL-PPR genes homologs. With the use of hybridological analysis a tight linkage of HRG01 and HRG02 marker fragments with the Rf1 gene controlling pollen fertility restoration trait was confirmed. The allelic variants of the RFL-PPR genes sequences were associated with the allelic state of the Rf1 locus. However, the CAPS marker elaborated for the QHL12D20 fragment showed independent inheritance from pollen fertility restoration trait in the F2 of the hybrid VIR116xVIR740.